Prevalence and risk factors of depression among older people living in nursing homes in Indonesia: A cross-sectional study - Patricia, Helena; Syed Elias, Sharifah Munirah; Binti Mohd Ali, Noor Azizah; Malini, Hema (Journal of Islamic, Social, Economics and Development, 2025)
Older people residing in nursing homes (NHs) experience challenging psychological, physiological, and social transformations that increase the prevalence of depression. The prevalence rates of depression among older people in NHs in Indonesia were indeterminate due to practical and data collection difficulties, as well as the limited research on depression and its related factors. This study aimed to determine the prevalence and risk factors of depression among older people living in NHs. This cross-sectional study was conducted from October to December 2023 and involved 183 older people aged 60 years or above living in NHs in Indonesia. Data was collected using the 15-Geriatric Depression Scale, the Physical Activity Scale for Older People, the UCLA Loneliness Scale, the Perceived Stress Scale, the Meaning in Life Questionnaire, the Multidimensional Scale of Perceived Social Support, and the IIUM Religiosity Scale. The data was analysed using the SPSS 22.0 version in the form of descriptive and inferential analysis. The study revealed that 69.9% of the participants had depression (48.1% mild, 18% moderate, 3.8% severe). The variables of physical activity (p= 0.000, r=-0.52), loneliness (p= 0.000, r=0.61), perceived stress (p= 0.001, r=0.25), meaningful existence (p= 0.000, r=-0.31), social support (p= 0.000, r=-0.69), and religiosity (p= 0.000, r=-0.59) were significantly associated with depression. The findings suggest that depression among older people living in NHs is influenced by a variety of factors, including physical activity, loneliness, perceived stress, meaningful existence, social support, and religiosity. Enhancing physical activity, social support, and religiosity, as well as addressing loneliness and perceived stress, may help in reducing depression in older people. Based on this study, healthcare professionals are recommended to consider the development of preventative methods such as modifying risk factors, promoting education programs, and developing future treatments, which could be advantageous.